Poola armee lahingud Punaarmee vastu Ilūkste maakonnas 1919. aasta septembris Poola vaatenurgast [The battles of the Polish Army against the Red Army in Ilūkste county in September 1919 from Poland’s viewpoint] - Jēkabsons, Ēriks (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2016)
The article describes a currently little-known episode in the history of the wars of independence of the Baltic countries and the Polish-Soviet war, where Polish Army and Lithuanian units fought against the Red Army at Daugavpils inSeptember 1919, with the Estonian and Latvian Rifle regiments forming the main part of the Red Army forces at Daugavpils. Within the composition of the Polish forces, a French tank company also took part in the battle. Th e Polish units as well as the Red Army suffered extensive losses in the battle. The situation was complicated by conflicts between Poland, Lithuania and Latvia, as all these countries deemed the Daugavpils region as a future part of their country. At the same time, tensions were also building between the Latvian Army and the West Russian Volunteer Army led by General Pavel Bermondt-Avalov. War broke out between them in October 1919. Immediately aft er the end of the battle of Daugavpils, six municipalities of the Ilūkste county in Courland were joined with Poland. At the beginning of 1920, the Polish and Latvian armies liberated Latgale. Th e Polish forces left Ilūkste county in the summer of 1920, when the fiercest battles of the Polish-Soviet war were being fought.